Global warming : the signs and the science - Kennard, David; Morissette, Alanis; Taylor, Michael; South Carolina Educational Television Network; Stonehaven Productions; PBS Home Video (2005)
This documentary profiles people who are living with the grave consequences of a changing climate, as well as the individuals, communities and scientists inventing new approaches to safeguard our children's future. Filmed across the U.S., Asia and South America, this program brings the reality of climate change to life and offers viewers a variety of ways to make a difference in their own communities.
Program originally broadcast on PBS on Nov. 2, 2005; DVD contains several additional interviews not included in the television broadcast, and lacks one scene that was included in the broadcast.
Editor, Scott Mason.
Hosted and narrated by Alanis Morissette.
DVD, widescreen.
Closed-captioned.
Keywords: Global warming; Greenhouse effect, Atmospheric; Climatic changes; Documentary television programs